2009
DOI: 10.1007/s10717-009-9148-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioceramic based on zirconium dioxide

Abstract: A bioinert ceramic based on partially stabilized tetragonal zirconium dioxide has been developed and its chemical and phase composition, microstructure, and physical -technical properties have been investigated. Ceramic heads for endoprostheses for the coxofemoral joint -28 mm in diameter with less than 0.02 mm roughness R a of the spherical surface and 1 mm deviation from sphericity -have been fabricated. It is shown that the bioceramic which has been developed and the ceramic heads for endoprostheses fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Such a sample of GCM was marked with ASZ-5 and was used for further research. The transformation strengthening of the glass matrix was carried out due to the controlled transition of tetragonal ZrO 2 to the monoclinic phase, which is accompanied by volume increase of 3 vol.% [11,12].…”
Section: Peculiarities Of Compositions and Technology Of Bioactive Gl...mentioning
confidence: 99%
“…Such a sample of GCM was marked with ASZ-5 and was used for further research. The transformation strengthening of the glass matrix was carried out due to the controlled transition of tetragonal ZrO 2 to the monoclinic phase, which is accompanied by volume increase of 3 vol.% [11,12].…”
Section: Peculiarities Of Compositions and Technology Of Bioactive Gl...mentioning
confidence: 99%
“…Высокими физическими характеристиками и отсутствием ток-сического воздействия на живые ткани обусловлена ценность этого материа-ла в тканевой инженерии. Биосовме-стимость керамики из диоксида цир-кония превышает аналогичное свой-ство титана [22,35].…”
Section: таблицаunclassified
“…The process employs an integrated approach to the synthesis of the starting powder and its molding and sintering [10]. With nanocrystalline zirconia powders, this is the only approach that may promote a new level of mechanical characteristics of the material and minimize the sintering temperature to provide submicron grain sizes, homogeneous chemical and phase compositions, and high density and microstructural homogeneity of ceramics.…”
mentioning
confidence: 99%
“…Technical tests on the experimental batch of these heads [10] have shown that they are made of ceramics based on tetragonal zirconia with density no less than 6.0 g/cm 3 , grain size no more than 400 nm, and bending strength no less than 600 MPa. The head diameter was 28 -0.02 mm, roughness of the spherical effective surface R a no more than 0.02 µm, and deviation from sphericity 1 µm.…”
mentioning
confidence: 99%